Knowledge and practice regarding diabetes and hypertension among elderly patients attending medicine out-patient department at Guru Nanak Dev Hospital, Amritsar - Kaur, Jasleen; Singh, Harpreet; Kalra, Riya Kaur; Kaur, Dania (International Journal Of Community Medicine And Public Health, 2017)
Background: According to the WHO fact sheet 2015, non-communicable diseases kill 38 million people each year globally. This preliminary study was undertaken in order to bring about healthy ageing. Methods: It is an observational study on 100 patients above 60 years of age belonging to the rural/urban community coming to the medicine OPD on a walk-in basis in the Government Medical College, Amritsar. Results: Out of the total 100 patients, 56 were male and 44 were female. Their awareness level was recorded on a self-designed questionnaire. Although 70% of the patients had one or the other disease under study (i.e. diabetes mellitus, hypertension), yet surprisingly their knowledge was limited to the symptoms they suffered from rather than the disease per se. Conclusions: As inferred from this study, the knowledge of the geriatric group about these diseases is limited, so there is an urgent need to create awareness among the patients and their family members as prevention will be far better than the cure in the long run.